PENGARUH PENAMBAHAN ABU KULIT KOPI ERMERA TIMOR-LESTE TERHADAP NILAI KUAT TEKAN BETON - Trindade Maia Gutteres da Silva; Made Yani Anggreni; Egidius Salu (Jurnal Teknik Gradien, 2023)
One of the waste materials which used as an additive for concrete mixtures is Coffee skin ash. Coffee skin ash is the result of burning coffee skin in the coffee bean grinding process. This waste is abundant in the Municipio Ermera (one of the big District in Timor-Leste), but its very limited to use. Municipio Ermera is a land and the center of coffee plantations in Timor-Leste. For this reason, an idea about use of wasted coffee skin ash is needed without causing damage to the environment. In this study, coffee skin ash used from Ermera area with a ratio of 0%, 5%, 10%, and 15% from cement weight. The purpose of this study to find how to compare the compressive strength of concrete between normal concrete and added coffee skin ash from Ermera. This method used in this study is experimental study and for each classification were made 5 specimens. The results of this research and analysis it can be concluded the compressive strength value of concrete using coffee skin ash as a partial replacement for cement composition with normal concrete has a significant comparison. Where it was found that concrete using coffee skin ash with composition of 5%, 10%, and 15% had a higher compressive strength value to concrete without coffee skin ash. The comparison of the increase in compressive strength that occurs is around 16% to 19,6%.